Doing justice: chinese civil procedure and its reform - Chen, Hangping (Civil Procedure Review, 2019)
This essay approaches the main aspects of Chinese civil procedure and the structure of the Judiciary in China in light of its latest legislative changes. The essay will then propose reforms to conciliate the search for speed and efficiency with the fundamental guarantees of the parties.